A linguistic analysis of selected speeches of Dr. Zakir Naik - Ismail, Anis Izzati; Othman, Khairiah (2015)
The English language is an effective medium to convey the message of Islam to educated and global audience. This study aimed to explore linguistic devices that contributed to effective speeches of a prominent Muslim speaker, Dr.Zakir Naik. Content analysis of two selected speeches of Dr.Zakir Naik was employed. The findings indicate that Dr.Zakir Naik mainly employed linguistic devices such as allusions, rhetorical questions, repetition, and parallelism to strengthen logical arguments, stir audience’s emotion, make message more memorable and correct misconceptions about Islam. It was also found that Dr.Zakir Naik utilized Islamic English to give the correct translation and transliteration of Arabic Islamic theological terms. The findings of this exploratory study provide essential theoretical and practical implications for future da’i to propagate Islam.